Upper bound on the speed of sound in nuclear matter from transport - Mauricio Hippert; Jorge Noronha; Paul Romatschke (Physics Letters B)
We point out that there is an upper bound on the speed of sound squared given by cs2≤0.781 valid for all known systems described by relativistic transient hydrodynamics where calculations of certain ratios of hydrodynamic transport coefficients can be performed from first principles. Assuming this bound is valid for ultradense matter implies that the maximum mass of isolated (non-rotating) neutron stars cannot be larger than 2.7 solar masses.